Response of six phytoplankton species in a high bicarbonate-containing culture medium spiked with gibberellic acid - Chowdhury, Chumki (Current Botany, 2025)
In the ocean and other aquatic bodies, phytoplankton plays a major role in fixing inorganic carbon in organic form. Anthropogenic input enhances the atmospheric carbon concentration, which leads to the dissolution of high amounts of carbon in water. In the present study, the response of five selected diatom species, Nitzschia longissima, Ditylum brightwellii, Asterionellopsis glacialis, Coscinodiscus radiatus, Skeletonema costatum, and one dinoflagellate species, Protoperidinium, were studied. The culture vessels spiked with gibberellic acid showed higher uptake relative to the control. Centric diatoms dominated over pinnate diatoms with respect to cell number in a high CO2 environment. Relative abundance of S. costatum was found to be 30-55% in the culture medium with gibberellic acid and 30-46% in the control among all the phytoplankton species. In a high CO2 environment, species specific positive response of phytoplankton may enhance the activity of the biological pump and hence turn the aquatic bodies into a sink for CO2.